Through My Lens: An Act of Telling in Exchange - Long, James; Amantea, Amy; Dicecco, Nico (Performance Matters, 2025)
Through My Lens is a participatory performance collaboratively developed by writer/performer Amy Amantea, media designer and operator Nico Dicecco, and writer/director James Long. This piece invites audience members to describe photos to Amy, who, besides being the performer, is also the photographer behind the images. Amy is also blind, having a total of 2 percent vision in one eye.This article incorporates written reflections, excerpts from a post-tour conversation, and text from one of the performances to explore three significant moments of interaction during the creation and staging of the piece: the first between Amy and the audience, the second between Amy and Nico as they developed a digital representation of Amy’s perception of sight, and the third between Amy and director and co-writer James, who continue to engage in ongoing discussions about the work’s function. At the centre of each exchange is a reflection on the power dynamics inherent in creating and performing a piece that equally prioritized the values of accessibility and exchange.Plain Language Abstract (adapted by Kelsie Acton with Daniel Foulds)Through My Lens is a performance made by three people:Amy Amantea, who wrote and performed Nico Dicecco, who made the pictures in the performance James Long, who wrote and directedIn this show, people from the audience are asked to describe photos to Amy. Amy is the person who took the photos. Amy is also legally blind with only some sight in one eye.This article is about how power is shared in a show that values access and the sharing of ideas. It looks at three moments to explore this:between Amy and the audience during the show between Amy and Nico as they worked in rehearsal to create a digital version of how Amy sees the world between Amy and James who talk about what the show should mean and do